1997
DOI: 10.1080/0144341970170111
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Teachers and Learning Style Preferences: action or watching in the classroom?

Abstract: The problematic issue in education is in applying learning styles research to classroom settings in schools where a range of teacher and student learning style preferences operate simultaneously. The preferred learning styles of secondary school teachers and managers were investigated using the Honey and Mumford model of learning styles. The Learning Styles Questionnaire (LSQ) developed by Honey and Mumford (1986) was used in this research. The LSQ identifies four learning style preferences: Activist, Reflecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Research has revealed that areas like beliefs, cultural background, teaching experiences, (Heimlich, 1990), the nature of the subject area (Evans, 2004;Lawrence, 1997), government curriculum initiatives (Hargreaves, 2003;Richards, 1998), and job satisfaction (Opdenakker & Van Damme, 2006) influence teaching styles. Researchers have attempted to design inventories to gauge teaching styles, but to date "little is known about teachers' use and perception of various teaching styles" (Kulinna & Cothran, 2003, p. 1).…”
Section: Teaching Style and Inventoriesmentioning
confidence: 99%
“…Research has revealed that areas like beliefs, cultural background, teaching experiences, (Heimlich, 1990), the nature of the subject area (Evans, 2004;Lawrence, 1997), government curriculum initiatives (Hargreaves, 2003;Richards, 1998), and job satisfaction (Opdenakker & Van Damme, 2006) influence teaching styles. Researchers have attempted to design inventories to gauge teaching styles, but to date "little is known about teachers' use and perception of various teaching styles" (Kulinna & Cothran, 2003, p. 1).…”
Section: Teaching Style and Inventoriesmentioning
confidence: 99%